Effect of teaching communication skills to medical undergraduate students: An exploratory study - Rakesh K Nayak; Deepti M Kadeangadi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Good communication skills are an essential component of physician training. Effective communication between the doctor and the patient leads to better compliance, better health outcomes, decreased litigation, and higher satisfaction both for doctors and patients. Traditional medical teaching imparts students with theoretical and practical knowledge of diseases process, diagnostic and treatment modalities but does not address communication skills, which are most essential in dealing with patients. Material and Methods: The present randomized control study was conducted in a Medical College of North Karnataka. A total of 60 students participated who were randomly assigned into two groups. Attitude toward learning communication skill was assessed using the Communication Skills Attitude Scale (CSAS). Pre- and post-assessment of communication skill was done using the Kalamazoo Essential Elements Communication Checklist. Results: All the study participants (n = 60) were 3rd-year MBBS students with the mean age of 21 ± 1.8 years. The CSAS median score for positive attitude was 57.5 and for negative attitude was 25 (minimum score = 13 and maximum score = 65). Significant difference was noted in the study group after training in communication skills (P < 0.01) compared to the control. Conclusion: Adequate training in communication does improve the skills of medical students and help in better relationship with patients.